2015
DOI: 10.1042/cs20140548
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone induces leucocyte migration by NADPH oxidase-driven ROS- and COX2-dependent mechanisms

Abstract: The mechanisms whereby testosterone increases cardiovascular risk are not clarified. However, oxidative stress and inflammation seem to be determinants. Herein, we sought to determine whether exogenous testosterone, at physiological levels, induces leucocyte migration, a central feature in immune and inflammatory responses and the mediating mechanisms. We hypothesized that testosterone induces leucocyte migration via NADPH oxidase (NADPHox)-driven reactive oxygen species (ROS) and cyclooxygenase (COX)-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
3

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 40 publications
1
32
0
3
Order By: Relevance
“…For instance, administration of exogenous testosterone increased NOX activity and expression in adult Wistar rats as well as leukocyte migration to the adventitia (15). These effects were inhibited with the addition of flutamide (AR antagonist) or apocynin (NOX inhibitor) (15). This suggests that androgen signaling is able to induce leukocyte migration through a NOX-dependent mechanism, which may contribute to both oxidative stress and immune cell infiltration in AAA.…”
Section: Androgen Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, administration of exogenous testosterone increased NOX activity and expression in adult Wistar rats as well as leukocyte migration to the adventitia (15). These effects were inhibited with the addition of flutamide (AR antagonist) or apocynin (NOX inhibitor) (15). This suggests that androgen signaling is able to induce leukocyte migration through a NOX-dependent mechanism, which may contribute to both oxidative stress and immune cell infiltration in AAA.…”
Section: Androgen Signalingmentioning
confidence: 99%
“…In opposition to estrogen signaling, androgen signaling increases NOX activity and expression. For instance, administration of exogenous testosterone increased NOX activity and expression in adult Wistar rats as well as leukocyte migration to the adventitia (15). These effects were inhibited with the addition of flutamide (AR antagonist) or apocynin (NOX inhibitor) (15).…”
Section: Androgen Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, long‐term treatment with testosterone, or with its non‐aromatizable androgen receptor agonist dihydrotestosterone, exacerbates endotoxin‐induced inflammation in the cerebral circulation by mechanisms that involve increased nuclear NF‐κB activation and increased levels of COX‐2 and inducible NOS (Gonzales et al ., ). Reinforcing a role for testosterone in vascular inflammation, data from our laboratory demonstrate that testosterone induces leukocyte migration by COX‐2‐dependent mechanisms (Chignalia et al ., ).…”
Section: Effects Of Sex Hormones On Prostanoid‐induced Vascular Respomentioning
confidence: 99%
“…Our group recently demonstrated that COX2-dependent ROS production is obligatory for testosterone-induced leukocyte migration (32), which may contribute to inflammation and vascular dysfunction. However, more studies on the role of androgens modulating COX-derived ROS and its implications for the cardiovascular system are warranted.…”
Section: Other Mechanisms: Testosterone and Ros Generation/oxidative mentioning
confidence: 99%